Pembentukan Persepsi Publik melalui Media Sosial terhadap Kebijakan Pemerintah Kota Makassar - Siti Nurul Haliza; Olvi Putri Dwi Irianti; Alimuddin Alimuddin; Moch Noer Alim Qalby (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Social media has become an influential digital public sphere in shaping public perceptions of local government policies, including those of the Makassar City Government. Advances in communication technology have transformed government communication from a one-way model into a more open, rapid, interactive, and participatory process. This study aims to analyze public perception formation through social media regarding Makassar City Government policies by examining digital communication patterns, public responses, opinion dynamics, and challenges in managing digital information. The study employs a descriptive qualitative approach through a literature review and analysis of relevant digital documentation concerning social media, government communication, public opinion, and local government policies. The findings show that social media plays a strategic role in expanding policy communication, accelerating information dissemination, and providing opportunities for public participation. However, it also presents challenges, including disinformation, public misunderstanding, opinion polarization, and negative perceptions when government communication is not managed adaptively and responsively. These findings highlight the importance of informative, transparent, dialogical, and ethical social media-based public communication to promote objective public understanding. Practically, the findings can guide the Makassar City Government in developing participatory digital communication strategies, strengthening public information management, anticipating disinformation, building public trust, and increasing public acceptance of policies. The study contributes theoretically to digital government communication and provides a reference for local governments in developing adaptive and responsive public communication policies in the digital era.